Fiscal Sustainability, Public Investment, and Growth in Natural Resource-Rich, Low-Income Countries : The Case of Cameroon - Samake, Issouf (IMF Working Papers; Working Paper, 2013)
This paper assesses the implications of the use of oil revenue for public investment on growth and fiscal sustainability in Cameroon. We develop a dynamic stochastic general equilibrium model to analyze the effects of such investment on growth and on the path of key fiscal indicators, such as the non-oil primary deficit and public debt. Policy scenarios show that Cameroon's large infrastructural needs and relatively low current debt levels could justify a temporary deviation from traditional policy advice that suggests saving part of the oil revenue to smooth expenditure over time. Model simulations show that a relatively high degree of efficiency of public investment is needed for scaled-up public investment to make a significant contribution to growth, while maintaining fiscal sustainability.